1999
DOI: 10.1002/(sici)1097-4628(19991017)74:3<490::aid-app3>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermomechanical mass spectroscopy for analysis of molecular and topological structure of rubber

Abstract: A novel method was applied to study the topological and molecular structures of multicomponent rubber. This method is based on the thermomechanical analysis of a solid polymer. A diblock amorphous structure was found for the studied rubber network. These blocks differ a great deal in their glass transition temperature. The methodology of how to calculate the crosslink density in each block, the molecular weight distribution of the chains between the junctions of the network, and the shares of low-temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
(5 reference statements)
4
20
0
Order By: Relevance
“…Two glass transitions and the bimodal MWD of the chains between the junctions of the vulcanizate containing a blend of cis-1,4-butadiene (BR) and cis-1,4-isoprene (NR) rubbers cured with sulfur and CBS as accelerator, was shown previous- 11 In the current work, when BR was replaced by EBR, the cured rubber in the indicated temperature interval also has two relaxation transitions ( Fig. 2).…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…Two glass transitions and the bimodal MWD of the chains between the junctions of the vulcanizate containing a blend of cis-1,4-butadiene (BR) and cis-1,4-isoprene (NR) rubbers cured with sulfur and CBS as accelerator, was shown previous- 11 In the current work, when BR was replaced by EBR, the cured rubber in the indicated temperature interval also has two relaxation transitions ( Fig. 2).…”
Section: Resultssupporting
confidence: 58%
“…For BR a difference in these temperatures is also about 200°C. 11 The presence of these blocks is probably determined by the different interaction energy of fragments of the chains with most of the active sites on the surface of carbon black particles. This conclusion is supported by nuclear magnetic resonance investigations of other rubbers 19 when it has been reported that more than two T 2 relaxation times are observed in carbon black-filled rubbers, reflecting the existence of rigid regions adjacent to the crosslinks or filler particle and soft regions distant from such rigid ones.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations